179 Relapsed Blastic Plasmacytoid Dendritic Cell Neoplasm vs Fungal Infection: Pitfalls in Pathology. (11th January 2018) - Dalland, Joanna; Piecoro, Dava; Kesler, Melissa; Wagner, Lars; Arora, Ranjana
Abstract: Objectives: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare clonal proliferation of immature plasmacytoid dendritic cells that most frequently presents as skin lesions. Methods: Chart review of a case of BPDCN was performed. Results: A 14-year-old girl presented with a one-year history of a right cheek red skin lesion with recent increased growth. Two months later two new red nodules appeared on the left breast and abdomen with multiple additional lesions scattered across her back. Biopsies showed atypical cellular infiltrates involving the dermis in a perivascular and peri-adnexal distribution. Immunohistochemical stains (IHC) showed strong positivity for CD56. Flow cytometry showed a large population expressing slightly reduced CD45, CD4, CD38, CD56, and CD33. This population was negative for CD3, CD5, CD7, CD8, CD30, CD34, CD117, CD19, CD20, CD14, CD16, and CD13. BPDCN was favored and chemotherapy was initiated. Two months later, she presented with a neutropenic fever. During her hospital course, two new red papules emerged on the forearm and abdomen, with similar clinical appearance as her original disease. A biopsy showed a dermal-based nodular lymphohistiocytic infiltrate with a perivascular and periadnexal distribution, reminiscent of her original disease. The infiltrate contained numerous small to large histiocytes with few CD3-positive T-lymphocytes. An increased number of CD4-positive histiocytes were present, but were negative for CD56, unlike the diagnostic specimen. A focal area of mixed inflammation with clear, pleomorphic round yeast like organisms were seen and GMS stain was positive for fungal organisms. Concurrent cultures were positive for Candida tropicalis . The lesions resolved with Fluconazole. Conclusion: The pattern of dermal involvement by BPDCN can be difficult to distinguish from other entities. Particularly in an immunosuppressed patient, infectious etiologies must be kept in the differential and IHC, flow cytometry, and culture should be utilized in diagnosis.